Diminutives as heads or specifiers: the mapping between syntax and phonology - Fábregas, Antonio (IBERIA: An International Journal of Theoretical Linguistics, 2014)
This article provides evidence for an analysis where the properties of lexical exponents are determined by the position they occupy in the structure and the configuration they establish with other items. It is argued that cross-linguistically and inter-linguistically, an item that can be introduced as a head or as a specifier displays syntactic, semantic and phonological properties that can be fully accounted for in the config- uration. The study concentrates on the case of diminutives in Spanish, German and Czech. We show, through different tests, that diminutives can be introduced as heads, in which case they form a Command Unit with the noun or adjective with which they combine, and can therefore change the semantic and grammatical properties of that base and phonologically integrate with it. In other cases they are introduced as spec- ifier, so that when phrasal movement of the base takes place they belong to different Command Units; in such cases they do not select for the base, they do not change its semantic or grammatical properties and they are not phonologically integrated with it. We argue that this account is superior to an analysis that uses any procedure where single lexical items are associated with sets of arbitrarily related properties.